Studi Literatur: Penggunaan Model Pembelajaran Problem Based Learning untuk Meningkatkan Kemampuan Berpikir Kritis Siswa SMP - Febrina Alamanda; Hafiizha Nur Addina; Sri Wahyuni (Peneliti.net, 2023)
Some schools still use conventional learning models as abasic strategy in learning. The conventional model can be in the form of conventional learning delivered using a lecture strategy. However, the conventional model is still not optimal in improving students’ critical thinking skills. To overcome this problem is to ulitize the Problem Based Learning model. PBL is a learning model based on the real world. PBL is more effective because it can develop student’s critical thinking skills. The strategy in this research is literature study and literature review. Literature study can be in the form of questions about plans, namely collecting related sources of information on a topic. The articles analyzed totaled 13 articles with a time span from 2018 to the latest in 2023. Based on the results of the analysis of the articles found, it was concluded that the use of PBL can improve students’ critical thinking skills.